Rancang Bangun Skuter Roda Tiga Minimalis Sebagai Sarana Logistik Dengan Kapasitas Beban Angkut Maksimal 200 Kg - Denta Firmanda; Mohammad Hakam; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Logistics plays an important role in commerce business and MSME (micro small and Medium Enterprises). Therefore we need a vehicle that helps in the transportation process of products to improve distribution. The vehicle is designed based on the needs of MSME which in general the vehicle will be operated on small urban and rural roads, so the design will consider the dimensions of the vehicle. Author uses Ulrich Method on the process of vehicle design. The Ulrich method is used because it can facilitate the process of product development that suits the target market. In this research, design and manufacture of chassis and supporting components for vehicle drive systems will be carried out. The structural analysis is using the Finite Element Method. In the design and analysis process, the author is assisted with Autodesk Fusion 360 Software. Based on the design, a minimalist three-wheeled scooter has a main dimension of 2227.3mm x 940mm x 967.2mm. After analyzing using the Finite Element Method on a chassis with vertical loading, it was found that the maximum stress is 73.83 MPa with value of safety facor is 3,38. Total production cost of the vehicle is twelve million six hundred and forty thousand rupiah